Terapi Menggambar Terhadap Fungsi Kognitif Dan Komunikasi Pada Lansia Dengan Demensia Literature Review - Bacthiar Safrudin; Dwi Widyastusi; Hanif Daffa Fauzan Rizki; Mohammad Ananta Pratama; Aji M.Ansyar; Amelia Kartika Sari; Raden Andi Rosa Tri Yulianti; annisa, natasya; Priska Cahya Ningtyas; Rhefita Yuniar; Nurfadilah Arman; Diazty (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
Dementia is a cognitive disorder that affects communication functions and the quality of life of older adults. One non-pharmacological approach that can be applied is drawing therapy. This therapy aims to stimulate cognitive function and improve communication skills in older adults with dementia. This study aims to analyze the effectiveness of drawing therapy in enhancing cognitive function and communication among elderly individuals with dementia. The method used is a literature review by analyzing previous research on the impact of drawing therapy on older adults with dementia. The results indicate that drawing therapy can help improve memory, attention, and verbal abilities in elderly individuals with dementia. Additionally, this therapy can reduce stress levels and enhance emotional well-being. Thus, drawing therapy can be an effective intervention in improving the quality of life of older adults with dementia.